A Novel miRNA Y-56 Targeting IGF-1R Mediates the Proliferation of Porcine Skeletal Muscle Satellite Cells Through AKT and ERK Pathways - Song, Jie; Hao, Linlin; Zeng, Xiangfang; Yang, Rui; Qiao, Shiyan; Wang, Chunli; Yu, Hao; Wang, Siyao; Jiao, Yingying; Jia, Hongyao; Liu, Songcai; Zhang, Ying (Frontiers in Veterinary Science, 2022)
As the key post-transcriptional regulators, miRNAs play an indispensable role in skeletal muscle development. The skeletal muscle satellite cells are the postnatal source of DNA contributed to growing muscle fibers. Thus, the goal of this study is to explore the effects of a novel miRNA Y-56 on the porcine skeletal muscle satellite cells (PSCs). We found that Y-56 was highly expressed in porcine muscle tissues, and its expression was higher in the Bama Xiang pig than the Landrace pig. The results showed that overexpression of Y-56 suppressed cell proliferation and cell cycle, whereas inhibition of Y-56 resulted in the opposite consequences. Meanwhile, Y-56 significantly inhibited the expression levels of cyclin dependent kinase 2 (CDK4), proliferating cell nuclear antigen (PCNA) and Cyclin D1. We identified that insulin like growth factor-1 receptor (IGF-1R) was a direct target of Y-56. Moreover, overexpression of IGF-1R promoted the cell proliferation and cell cycle process of the PSCs, as well as up-regulated the expressions of CDK4, PCNA and Cyclin D1. On the contrary, knock-down of IGF-1R was associated with the opposite tend. Furtherly, overexpression of IGF-1R partially reversed the inhibition of cell proliferation and cell cycle process of the PSCs and the down-regulation of the expression of CDK4, PCNA and Cyclin D1, which caused by overexpression of Y-56. Finally, western blotting results showed that Y-56 inhibited the expression level of p-AKT and p-ERK. Collectively, our findings suggested that Y-56 represses proliferation and cell cycle process of the PSCs through targeting IGF-1R-mediated AKT and ERK pathways.